ENaC in Cholinergic Brush Cells - Kandel, Chrissy; Schmidt, Patricia; Perniss, Alexander; Keshavarz, Maryam; Scholz, Paul; Osterloh, Sabrina; Althaus, Mike; Kummer, Wolfgang; Deckmann, Klaus (Frontiers in Cell and Developmental Biology, 2018)
Cholinergic polymodal chemosensory cells in the mammalian urethra (urethral brush cells = UBC) functionally express the canonical bitter and umami taste transduction signaling cascade. Here, we aimed to determine whether UBC are functionally equipped for the perception of salt through ENaC (epithelial sodium channel). Cholinergic UBC were isolated from ChAT-eGFP reporter mice (ChAT = choline acetyltransferase). RT-PCR showed mRNA expression of ENaC subunits Scnn1a, Scnn1b, and Scnn1g in urethral epithelium and isolated UBC. Scnn1a could also be detected by next generation sequencing in 4/6 (66%) single UBC, two of them also expressed the bitter receptor Tas2R108. Strong expression of Scnn1a was seen in some urothelial umbrella cells and in 65% of UBC (30/46 cells) in a Scnn1a reporter mouse strain. Intracellular [Ca2+] was recorded in isolated UBC stimulated with the bitter substance denatonium benzoate (25 mM), ATP (0.5 mM) and NaCl (50 mM); mannitol (150 mM) served as osmolarity control. NaCl, but not mannitol, evoked an increase in intracellular [Ca2+] in 70% of the tested UBC. The NaCl-induced effect was blocked by the ENaC inhibitor amiloride (IC50 0.47 µM). When responses to both NaCl and denatonium were tested, all three possible positive response patterns occurred in a balanced distribution: 42% NaCl only, 33% denatonium only, 25% to both stimuli. A similar reaction pattern was observed with ATP and NaCl as test stimuli. About 22% of the UBC reacted to all three stimuli. Thus, NaCl evokes calcium responses in several UBC, likely involving an amiloride-sensitive channel containing α-ENaC. This feature does not define a new subpopulation of UBC, but rather emphasizes their polymodal character. The actual function of α-ENaC in cholinergic UBC – salt perception, homeostatic ion transport, mechanoreception – remains to be determined.